INFLUENCE OF TECHNOLOGICAL NON-METALLIC PRODUCTION WASTES ON HEAVY WEIGHT CONCRETE PROPERTIES - V. F. Akhtyamov; E. N. Khafizova (Вестник СибАДИ, 2018)
Introduction. The following article deals with recycling of non-metallic industrial wastes for the production of heavy weight concretes.Materials and methods. The research uses a set of standard methods.Results. The physical, chemical characteristics and screenings gradation of the quarries Sverdlovsk and Chelyabinsk regions are explored. The compositions of effective heavy weight concretes with strength quality В22, 5-В40 based on stone screening dust and additives MC-Power Flow and Centrament Air 202 have been developed. The structural properties and construction characteristics of concrete mixtures and heavy weight concretes with stone screening dust are studied. The research demonstrates that the addition of MC-Power Flow additive to the concrete mixture in an amount of 0.4 to 0.8 % (by weight of cement) allows to reduce the hardness of the mixture from 26 to 5 seconds and promotes the creation of a tight contact zone at the surface of the aggregate. Moreover, the influence of the complex additive on the pore parameters of heavy weight concrete and on the frost resistance of samples is determined with the use of screening from rocks as a fine aggregate. Samples of heavy concrete frost resistance grade F300 are obtained.Discussion and conclusion. Cost-effectiveness analysis of the screenings use in the composition of heavy weight concrete and the industrial approbation at the precast concrete factory of the Tyumen region are carried out.